Low loss, fully-printed, ferroelectric varactors for high-power impedance matching at low ISM band frequency. Issue 7 (23rd May 2019) - Kienemund, Daniel; Bohn, Nicole; Fink, Thomas; Abrecht, Mike; Bigler, Walter; Binder, Joachim R.; Jakoby, Rolf; Maune, Holger
Abstract: Low loss, ferroelectric, fully-printed varactors for high-power matching applications are presented. Piezoelectric-induced acoustic resonances reduce the power handling capabilities of these varactors by lowering the Q -factor at the operational frequency of 13.56 MHz. Here, a quality factor of maximum 142 is achieved with an interference-based acoustic suppression approach utilizing double metal–insulator–metal structures. The varactors show a tunability of maximum 34% at 300 W of input power. At a power level of 1 kW, the acoustic suppression technique greatly reduces the dissipated power by 62% from 37 W of a previous design to 14.2 W. At this power level, the varactors remain tunable with maximum 18.2% and 200 V of biasing voltage.